Induction of Oral Tolerance with Transgenic Plants Expressing Antigens for Prevention/Treatment of Autoimmune, Allergic and Inflammatory Diseases - Ma, Shengwu; Liao, Yu-Cai; M. Jevnikar, Anthony (Current Pharmaceutical Biotechnology, 2015)
The prevalence and incidence of autoimmune and allergic diseases have increased dramatically over the last several decades, especially in the developed world. The treatment of autoimmune and allergic diseases is typically with the use of non-specific immunosuppressive agents that compromise the integrity of the host immune system and therefore, increase the risk of infections. Antigenspecific immunotherapy by reinstating immunological tolerance towards self antigens without compromising immune functions is a much desired goal for the treatment of autoimmune and allergic diseases. Mucosal administration of antigen is a long-recognized method of inducing antigen-specific immune tolerance known as oral tolerance, which is viewed as having promising potential in the treatment of autoimmune and allergic diseases. Plant-based expression and delivery of recombinant antigens provide a promising new platform to induce oral tolerance, having considerable advantages including reduced cost and increased safety. Indeed, in recent years the use of tolerogenic plants for oral tolerance induction has attracted increasing attention, and considerable progress has been made. This review summarizes recent advances in using plants to deliver tolerogens for induction of oral tolerance in the treatment of autoimmune, allergic and inflammatory diseases.
Keywords: allergy